Body Image Dan Pembentukan Rasa Percaya Diri Siswa SMP: Analisis Pengalaman Subjektif - Dyah Ayu Ratna Angely; Elisabeth Christiana (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2026)
This study aims to analyze the role of body image in shaping self-confidence among junior high school students. The study employed a qualitative approach using a case study method. The participants consisted of four students at SMP Negeri 35 Surabaya who were identified as having low self-confidence due to perceptions of physical appearance. Data were collected through semi-structured interviews and analyzed using data reduction, data display, and conclusion drawing techniques. Data validity was strengthened through source triangulation involving guidance and counseling teachers and homeroom teachers. The findings indicate that students’ body image lies on a spectrum between self-acceptance and dissatisfaction with certain body parts, influenced by internal and external factors. Students with positive body image tend to have better self-confidence, while negative body image is associated with feelings of shame, anxiety, and a tendency to withdraw. This study concludes that body image plays an important role in shaping junior high school students’ self-confidence.